Pendampingan Ibu PKK dalam Penguatan Peran sebagai Pendidik Keluarga untuk Peningkatan Literasi dan Pendidikan Karakter Anak di Kelurahan Pamusian - Fathonah, Siti; Apriani, Eva (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The family is the first and primary educational environment for children. Mothers play a central role as educators within the family. However, in today's digital era, many Family Welfare Movement (PKK) mothers in Pamusian Village face challenges in assisting their children in learning and developing their character. This community service program aims to improve the knowledge and skills of PKK mothers in Pamusian Village in carrying out their family education function through mentoring methods. Activities included training, group discussions, and direct mentoring for 20 PKK members. Results showed a 78% increase in PKK mothers' understanding of educational techniques, digital literacy, and character education. PKK mothers were also able to develop a